2006
DOI: 10.3164/jcbn.38.59
|View full text |Cite
|
Sign up to set email alerts
|

The Health Effects of Tea Polyphenols and Their Antioxidant Mechanism

Abstract: Summary There are thousands year of history for drinking tea in China and world. The benefits of drinking tea to human health are well known and improved by epidemiological result and experiments. The most effective components in tea are polyphenols which are about 30% weight of dry tea. The antitumor and antimutagenic effects of the tea polyphenols, the prevent effect of the tea polyphenols on Alzheimer's disease and Parkinson's disease, the protective effects of the tea polyphenols on neuron against lead tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 62 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…Green tea, which has polyphenols as a principal constituent, has been drunk widely in Japan and China for more than 5000 years [ 24 ]. It has been reported that the polyphenols in green tea have anti-tumor effects [ 16 , 17 ], and epidemiologically those who drink green tea regularly have a lower risk of cancer. Those who drink 10 cups or more of green tea every day have a lower risk of gastric cancer compared with those having a lesser intake[ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green tea, which has polyphenols as a principal constituent, has been drunk widely in Japan and China for more than 5000 years [ 24 ]. It has been reported that the polyphenols in green tea have anti-tumor effects [ 16 , 17 ], and epidemiologically those who drink green tea regularly have a lower risk of cancer. Those who drink 10 cups or more of green tea every day have a lower risk of gastric cancer compared with those having a lesser intake[ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Green tea polyphenols (GTP), which are compounds in Japanese green tea, are reported to have bactericidal properties against pathogenic bacteria in food and also have anti-tumor effects; attention has been given to their application as a new treatment for infectious diseases and malignant neoplasm [ 16 , 17 ]. In this study, we examined the effects of GTP on gastric proliferation and apoptosis in an H. pylori -infected mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…The growing evidence towards the health benefits of tea has resulted in extensive studies to unravel the scientific basis of the healing and curing power of tea 3,4. A well accepted scientific consensus that is emanating from several scientific investigations is that tea contains high levels of antioxidant polyphenols, including flavonoids, and catechins, and all of which scavenge the dangerous free radicals in the body and thus, prevent the progress of various diseases 25-34. Polyphenolic flavonoids in tea (Fig 1), of which epigallocatechin gallate (EGCG) is the second major constituent, has anticarcinogenic activity in vitro which may support the results of the epidemiologic research on the correlation between drinking tea and the risk of morbidity from cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Green tea is widely consumed in the eastern world. Studies have shown that green tea possess diverse pharmacological properties that include anti-oxidative, anti-inflammatory, anti-carcinogenic, anti-arteriosclerotic and anti-bacterial effects [ 8 11 ]. Several previous studies demonstrated the inhibitory effects of green tea on NV in the vascular changes of the eye.…”
Section: Introductionmentioning
confidence: 99%